Trade Effects of Customs Reform : Evidence from Albania - Fernandes, Ana M.; Hillberry, Russell; Mendoza Alcántara, Alejandra (World Bank Group, Washington, DC, 2015)
Despite enormous academic interest in international trade costs and keen policy interest in efforts to mitigate them, so far there is very little hard evidence on the impacts of trade facilitation efforts. This paper exploits a dramatic reduction in the rate of physical inspections by Albanian customs to estimate the effects of fewer inspection-related delays on the level and composition of imports. In this setting, the paper finds evidence that the expected median number of days spent in Albanian customs falls by 7 percent when the probability that a shipment is inspected falls from 50 percent or more to under 50 percent. In turn, this reduction in time produces a 7 percent increase in import value. The paper finds evidence that the reforms favored imports from preferential trading partners, especially the European Union. There are also reform-induced changes in the composition of trade, including increases in average quantities and unit prices, the number of shipments, and the number of importing firms per product-country pair and the number of countries per firm-product pair. A back-of-the-envelope calculation suggests that the estimate of 7 percent import growth along an intensive margin is roughly consistent with a 0.36 percentage point reduction in average tariff equivalent trade costs. Applying this figure to the value of Albania's non-oil imports produces a reform-induced trade cost savings estimate of approximately US$12 million in 2012.